The budget of carbon in the farming of the Amazon river prawn and tambaqui fish in earthen pond monoculture and integrated multitrophic systems - Flickinger, Dallas L. [UNESP]; Costa, Gelcirene A. [UNESP]; Dantas, Daniela P. [UNESP]; Proença, Danilo C. [UNESP]; David, Fernanda S. [UNESP]; Durborow, Robert M.; Moraes-Valenti, Patricia [UNESP]; Valenti, Wagner C. [UNESP] (Elsevier, 2020)
The present study analyzed the inputs, outputs, and accumulation of carbon in ecological compartments of earthen ponds for the grow-out of Amazon river prawn (Macrobrachium amazonicum) and tambaqui fish (Colossoma macropomum) reared in monoculture and integrated multi-trophic aquaculture (IMTA) systems, using recycled hypereutrophic water. A completely randomized experiment was designed with four treatments and three replications: PM- monoculture with 30 prawn m−2, FM- monoculture with 3 fish m−2, IMTA- fish-prawn polyculture with 30 prawn m−2 and 3 fish m−2 reared free-swimming, POLY-CAGE- fish-prawn IMTA with 30 prawn m−2 reared free-swimming and 40 fish m−3 in net-cages. Animals, rain, water, feed, soil, gases, total suspended solids, settleable solids, and accumulated sludge were collected throughout the experiment to determine their total organic and total inorganic carbon contents and to calculate the carbon budget. Results showed that much of the carbon accumulated as solid organic material (∼55 – 84%) and animal biomass (∼4 – 18%). The remaining carbon was discharged to receiving water bodies in the outlet water during harvesting (∼6 – 8%) or emitted as carbon dioxide (CO2) and methane (CH4) (∼1 – 5%). Feed management appeared to influence the major biological processes in the aquatic carbon cycle, such as photosynthesis and aerobic decomposition. All systems showed absorption of atmospheric CO2 (∼529 – 782 kg C-CO2 ha−1) that was higher than the emissions (∼35 – 93 kg C-CO2 ha−1) and CH4 (∼14 – 123 kg C-CH4 ha−1). Furthermore, all of the culture processes in the present study removed ∼1,000 to 2,000 kg Total Carbon ha−1 from the inlet water, and thus, these systems can provide important ecosystem services. The high accumulation of carbon in the settleable solids (∼69% of outputs) and the adequate water quality maintained in the IMTA demonstrate the resilience of this grow-out system to high allochthonous inputs of organic matter as feed. An increased prawn density or the addition of a mud-feeder species to the culture may enhance the incorporation of carbon from settleable solids into harvested biomass, improving the efficiency of the systems.
Keywords: Carbon; carbon sequestration; IMTA; in ponds; Macrobrachium Colossoma